2012
DOI: 10.3390/ijms131216796
|View full text |Cite
|
Sign up to set email alerts
|

Actinopyga lecanora Hydrolysates as Natural Antibacterial Agents

Abstract: Actinopyga lecanora, a type of sea cucumber commonly known as stone fish with relatively high protein content, was explored as raw material for bioactive peptides production. Six proteolytic enzymes, namely alcalase, papain, pepsin, trypsin, bromelain and flavourzyme were used to hydrolyze A. lecanora at different times and their respective degrees of hydrolysis (DH) were calculated. Subsequently, antibacterial activity of the A. lecanora hydrolysates, against some common pathogenic Gram positive bacteria (Bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 38 publications
(42 reference statements)
1
31
0
Order By: Relevance
“…Antimicrobial peptides from natural sources can be promising candidates to replace synthetic antimicrobial agents in the treatment of a wide spectrum of bacterial infections. Thus, Ghanbari et al (2012) explored the application of Actinopyga lecanora (sea cucumber) in the production of antimicrobial peptide. They found that after 7 h of hydrolysis, hydrolysates prepared by bromelain exhibited the highest antimicrobial activities against Pseudomonas sp., Pseudomonas aeruginosa, and Escherichia coli compared to other hydrolysates generated by papain, alcalase, pepsin, trypsin, and flavorzyme.…”
Section: Protein Hydrolysatementioning
confidence: 99%
“…Antimicrobial peptides from natural sources can be promising candidates to replace synthetic antimicrobial agents in the treatment of a wide spectrum of bacterial infections. Thus, Ghanbari et al (2012) explored the application of Actinopyga lecanora (sea cucumber) in the production of antimicrobial peptide. They found that after 7 h of hydrolysis, hydrolysates prepared by bromelain exhibited the highest antimicrobial activities against Pseudomonas sp., Pseudomonas aeruginosa, and Escherichia coli compared to other hydrolysates generated by papain, alcalase, pepsin, trypsin, and flavorzyme.…”
Section: Protein Hydrolysatementioning
confidence: 99%
“…Many of AMPs are derived from larger proteins that could be enzymatically digested and produce active fragments. This has been demonstrated by Ghanbari et al [25]. In fact, by digesting the tissues of sea cucumber Actinopyga lecanora with bromelain, peptides with inhibitory activities against respectively Pseudomonas sp., P. aeruginosa and E. coli were obtained and one papain digested fraction showed antibacterial activity against S. aureus.…”
Section: Antimicrobial Peptides In Echinodermsmentioning
confidence: 81%
“…Many AMPs are derived from larger proteins that could be enzymatically digested and produce active fragments. This has been demonstrated by (Ghanbari et al 2012). In fact, digesting the tissues of sea cucumber Actinopyga lecanora (Jaeger, 1833) with bromelain, peptides with inhibitory activities against Pseudomonas sp., P. aeruginosa, and Escherichia coli, respectively, were obtained and one papain-digested fraction showed antibacterial activity against Staphylococcus aureus.…”
Section: Antimicrobial and Antibiofilm Peptides In Echinodermsmentioning
confidence: 92%